Perceived risk and risk reduction behaviors in fish and seafood consumption - Soyoung An; Thomas Eck; Jinkyung Choi (Frontiers in Sustainable Food Systems, 2024)
This study aimed to explore what risk factors consumers perceive when consuming fish and seafood at a time when treated wastewater was being discharged. Moreover, this study attempted to examine what risk reduction behaviors consumers take to minimize these risk factors. The data was collected online for one week in September 2023 and 334 responses from Korean consumers were used for the analysis. Five risk dimensions were identified: biochemical risk, hygiene risk, environmental risk, value risk, and socio-phycological risk were identified. Higher levels of perceived risks were identified in female respondents and four dimensions of risk (except hygiene risk) showed a significant relationship with risk reduction behavior. Such risk reduction behavior significantly influenced the intention to consume seafood. Practical and theoretical implications were also suggested from the findings of this study.